2022
DOI: 10.1038/s41394-022-00551-5
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to and impact of home-based high-intensity IMT in people with spinal cord injury: a pilot study

Abstract: Study design The pilot study was completed in 5 phases (Control and 4 phases of IMT) incorporating assessments at Baseline 1 (BL1), BL2, Follow-up 1 (F1), F2, F3, and F4. Objective To assess the adherence and impact of a daily high-intensity (80% of max) inspiratory muscle training (IMT) home program with once weekly supervision for people with spinal cord injury (SCI). Setting Assessments: research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Characteristics used as criteria for matching did not differ significantly between groups (height or adherence), however people in the F-IMT group were younger ( p = 0.002), had a shorter duration of injury ( p = 0.002), weighed less ( p = 0.030), and had a higher PI max ( p = 0.041) at baseline than the T-IMT group (Table 3 ). Further descriptive information about the overall trial samples can be found in the original publications [ 4 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics used as criteria for matching did not differ significantly between groups (height or adherence), however people in the F-IMT group were younger ( p = 0.002), had a shorter duration of injury ( p = 0.002), weighed less ( p = 0.030), and had a higher PI max ( p = 0.041) at baseline than the T-IMT group (Table 3 ). Further descriptive information about the overall trial samples can be found in the original publications [ 4 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inspiratory muscle strength outcomes in two published original IMT studies in people with chronic SCI were compared. One study [ 4 ] used F-IMT (PrO2, PrO2Fit, Smithfield, RI, USA) and the second [ 7 ] used T-IMT (Threshold-IMT, Philips Respironics, Chichester, UK). Both studies had approval from affiliated human research ethics boards and were registered prior to trial commencement (NCT04210063; ANZCTR12612000929808).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations